Rekonstruksi Makna Kesepian dan Isolasi Sosial di Rumah Lansia Bakti Kasih Siti Anna melalui Dukungan Sosial: Analisis Interaksionisme Simbolik - Nadia, Nadia; Elza, Elza; Hidayati, Hidayati; desmaisi, Desmaisi (Jurnal Empirika, 2026)
Abstract Loneliness and social isolation are common issues among older adults, arising from declining social interactions and shifting modern family structures. This study aims to reconstruct the meaning of loneliness and social isolation among residents of the Bakti Kasih Siti Anna Elderly Home through their experiences of social support, using a symbolic interactionism perspective. A qualitative phenomenological approach was employed through in-depth interviews and participant observation to capture how meanings are formed within daily interactions. The findings indicate that loneliness is understood as a loss of meaningful relationships, while social support introduces symbols of care and recognition that reinforce the elders’ social identity. The study concludes that the negative meaning of loneliness is not static; through continuous symbolic interactions and meaningful social support, older adults can reconstruct a sense of connectedness and strengthen their social integration.